2022
DOI: 10.1136/bmjopen-2021-059983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on maternal healthcare indices in Southern Iran: an interrupted time series analysis

Abstract: ObjectivesEpidemics are anticipated to influence the coverage of health services. We assessed the impact of the COVID-19 pandemic on maternal healthcare indices and care providers’ performance.Setting1801 maternal healthcare centres under the auspices of Shiraz University of Medical Sciences, Shiraz, Southern Iran.ParticipantsApproximately 63 000 pregnant women.Primary and secondary outcome measuresIn this prospective ecological study, interrupted time series analysis was used to model and compare the trend of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Previous studies showed that most maternal healthcare indices sharply declined with the announcement of the COVID-19 pandemic in Iran but soon started to recover after a gap of 1 to 2 months. 27 Two studies in India, like our study, reported an increase in stillbirths during the COVID-19 lockdown period. In this study, the lack of prenatal care and lack of access to the urgent transfer system to the hospitals were mentioned as one of the possible main risk factors for this increase.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies showed that most maternal healthcare indices sharply declined with the announcement of the COVID-19 pandemic in Iran but soon started to recover after a gap of 1 to 2 months. 27 Two studies in India, like our study, reported an increase in stillbirths during the COVID-19 lockdown period. In this study, the lack of prenatal care and lack of access to the urgent transfer system to the hospitals were mentioned as one of the possible main risk factors for this increase.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies showed that most maternal healthcare indices sharply declined with the announcement of the COVID-19 pandemic in Iran but soon started to recover after a gap of 1 to 2 months. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, 14 studies reported data from four low-income countries ( 34–47 ), 21 studies were focused on 13 lower-middle income countries ( 48–68 ), seven studies were conducted in five upper-middle income countries ( 69–75 ) and three were multi-centred ( 76–78 ). Out of 45 included studies, 11 studies were cross-sectional ( 41 , 45 , 48 , 51 , 55–57 , 65 , 69 , 70 , 76 ), 14 were pre-post studies ( 34 , 38 , 49 , 50 , 52 , 53 , 56 , 62 , 64 , 72–75 , 77 ), nine were time-series ( 35 , 37 , 39 , 43 , 58 , 59 , 67 , 71 , 78 ), five were mixed methods ( 36 , 42 , 47 , 61 , 63 ) and six were qualitative ( 40 , 44 , 46 , 54 , 60 , 68 ). The included studies’ characteristics are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In nine studies ( 34 , 38 , 41 , 47 , 49 , 58 , 67 , 76 , 77 ), the analysis showed interruptions in family planning services ( 76 ), a decrease in attendance of family planning visits ( 77 ), in the overall number of such visits ( 34 , 41 , 47 , 49 , 58 , 67 ) and family planning acceptance rate ( 38 ) compared to the pre-COVID-19 levels. Although some authors observed a reduction in the number of new contraceptive acceptors ( 45 ) and difficulties accessing contraceptives ( 73 ), Tilahun and colleagues reported an increased contraceptive acceptance rate in Ethiopia ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…The segmented Poisson regression was selected since each dependent variable was constituted from the counts of care delivered in a season. The interrupted time series models require at least three independent variables [ 22 ]: …”
Section: Methodsmentioning
confidence: 99%